Analysis of Non-pharmacological Management Strategies for Stable Chronic Obstructive Pulmonary Disease Based on 2021 GOLD's Global Strategy for the Diagnosis，Management，and Prevention of Chronic Obstructive Pulmonary Disease - LI Zhenghuan, ZHANG Xiaoyun, CHEN Yang, SONG Xueli, LIU Xin (Zhongguo quanke yixue, 2022)
Chronic obstructive pulmonary disease (COPD) is now the third leading cause of death in the world, after ischemic heart disease and stroke. However, in the face of this preventable and curable major public health problem, there are still many problems in clinical diagnosis and treatment in China, such as insufficient health education, missing follow-up data, and non-standardized clinical management, which may be important causes of the deterioration of conditions, leading to increased difficulties in treating and higher possibility of poor outcome after late treatment as well as increased social and economic burden of COPD. Therefore, it is of great practical significance to accelerate the standardization of prevention, diagnosis and management of COPD to improve the accuracy and effectiveness of diagnosis and treatment of COPD. To provide a reference for emergency and respiratory clinicians to better treat COPD patients clinically, in view of domestic diagnosis, treatment and studies regarding COPD, we comprehensively analyzed the non-pharmacological treatment of stable COPD based on the updated GOLD's Global Strategy for the Diagnosis, Management, and Prevention of Chronic Obstructive Pulmonary Disease, mainly including pulmonary function measurement and assessment, smoking cessation, pulmonary rehabilitation, oxygen therapy, ventilatory support and surgical interventions.